Commitment to Changing Services to Be the Best for Championing (Innovative) Behavior Post-Accreditation SNARS Version at Gambiran Regional Hospital, Kediri City - Erik Prastyanto; Ratna Wardani; Agustin Widyowati; Ardi Bastian (Universitas STRADA Indonesia, 2024)
The growth of hospitals creates increasingly fierce competition and customers increasingly have selective choices, and this is a challenge that will affect the sustainability of the organization. Alternative competitive strategies are needed for hospitals to improve the quality and quality of services through accreditation assessments. Post-accreditation results from hospitals alone will not be enough to be balanced with a commitment to change services for the better. Good commitment will give rise to championing behavior in facing increasingly dynamic environmental changes. Research purposes. Analyzing the relationship between commitment to changing services to the best and championing (innovative) behavior after SNARS version accreditation at Gambiran Regional Hospital, Kediri City. Research methods. Quantitative research with correlational design. The population in this study were ASN nurse employees at Gambiran Regional Hospital, Kediri City with a sample of 122 respondents using the Proportional Random Sampling technique. The independent variable is commitment to change and the dependent variable is championing behavior. Data collection used questionnaires and Spearman correlation analysis. Research result. The results of the Spearman correlation test analysis showed that there was no relationship between commitment and Championing (p value 0.569 > 0.05). Conclusion. The innovative behavior of ASN employees is influenced by many factors, not only in terms of organizational commitment